The Vastus Lateralis Muscle Interstitium Proteome Changes after an Acute Nociception in Patients with Fibromyalgia Compared to Healthy Subjects—A Microdialysis Study - Ghafouri, Bijar; Matikhan, Daria; Christidis, Nikolaos; Ernberg, Malin; Kosek, Eva; Mannerkorpi, Kaisa; Gerdle, Björn; Wåhlén, Karin (Biomedicines, 2023)
Fibromyalgia (FM) is a complex disorder and a clinical challenge to diagnose and treat. Microdialysis is a valuable tool that has been used to investigate the interstitial proteins and metabolites of muscle in patients with fibromyalgia. The implantation of the catheter in the muscle causes acute tissue trauma and nociception. The aim of this study was to investigate acute proteome changes in the vastus lateralis muscle in women fibromyalgia patients (FM) and healthy subjects (CON). A further aim was to study if a 15-week resistance exercise program in FM had any influence on how chronic painful muscle responds to acute nociception. Twenty-six women patients with FM and twenty-eight CON were included in this study. A microdialysis catheter (100 kilo Dalton cut off, membrane 30 mm) was inserted in the vastus lateralis muscle, and samples were collected every 20 min. Subjects rated pain before catheter insertion, directly after, and every 20 min of sample collection. Dialysate samples from time points 0–120 were pooled and considered trauma samples due to the catheter insertion. The samples were analyzed with nano-liquid chromatography-tandem mass spectrometry (nLC-MS/MS). Advanced multivariate data analysis was used to investigate protein profile changes between the groups. Multivariate data analysis showed significant (CV-ANOVA p = 0.036) discrimination between FM and CON based on changes in 26 proteins. After the 15-week exercise intervention, the expression levels of the 15 proteins involved in muscle contraction, response to stimulus, stress, and immune system were increased to the same expression levels as in CON. In conclusion, this study shows that microdialysis, in combination with proteomics, can provide new insights into the interstitial proteome in the muscle of FM. In response to acute nociception, exercise may alter the innate reactivity in FM. Exercise may also modulate peripheral muscle proteins related to muscle contraction, stress, and immune response in patients with FM.